Lithium-rich alloy for high-specific-energy battery and preparation method of lithium-rich alloy
By preparing a lithium-rich alloy and refining its second phase distribution in the alloy, the problems of lithium dendrites growth and volume expansion in lithium metal batteries are solved, and the circulation performance and production efficiency of lithium metal batteries are significantly improved.
Patent Information
- Application Number
- CN202411364822.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-14
AI Technical Summary
Among existing lithium metal batteries, pure lithium sheets have problems such as lithium dendrites growth, volume expansion, and uneven lithium deposition during use, which seriously hinders the application of lithium metal batteries.
A lithium-rich alloy for high-specific energy batteries and its preparation method are adopted. By reacting pure lithium ingots with metal elements (such as Al or Mg) at high temperatures, forming an alloy mixture liquid, and then casting, rolling, cutting and heat treatment, refine the second phase to improve its distribution uniformity in the alloy.
By refining the second phase, the uniformity of nucleation during lithium deposition is improved, the formation of lithium dendrites is inhibited, the circulation performance of lithium metal batteries is significantly improved, the production process is simplified, and the production efficiency is improved.
Smart Images

Figure CN119433398A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery manufacturing, and in particular relates to a lithium-rich alloy for a high-energy-density battery and a preparation method thereof. Background Art
[0002] Lithium metal batteries have become an important research direction for future energy storage devices due to their high energy density and high capacity. Lithium metal batteries generally use pure lithium sheets as negative electrodes, but during the use of pure lithium sheets, there are problems such as lithium dendrite growth, volume expansion, and lithium deposition, which seriously hinder the future application of lithium metal batteries.
[0003] In order to solve the above problems, people have made great efforts, such as using lithium-based alloys to replace pure lithium sheets. Lithium-based alloys have been shown to play an important role in inhibiting the growth of lithium dendrites, controlling interfacial reactions, and improving Coulomb efficiency (CE) and cycle life. Conventional lithium alloy negative electrode materials and preparation methods disclosed in application number CN201811166961.4, the prepared lithium alloy negative electrode can not only limit lithium dendrites, but also the copper nanowire network provides sufficient space for lithium deposition, and also inhibits the change in battery volume during the deposition and dissolution of metallic lithium. However, according to the SEM photos of the lithium alloy negative electrode of the technical solution, the second phase particles are larger in size, and their distribution in the pole piece is more dispersed, which can easily lead to uneven growth of lithium dendrites, rapid local volume changes, and uneven distribution of the conductive network. There is still room for improvement. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a lithium-rich alloy for high-energy-density batteries and a preparation method thereof, which can refine the second phase and make the distribution of the second phase in the alloy more uniform, thereby helping to improve the cycle performance of lithium metal batteries.
[0005] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a lithium-rich alloy for a high specific energy battery, comprising the following steps:
[0006] S1. Put a certain mass of pure lithium ingot into a stainless steel crucible and heat it to 300-500°C until the pure lithium ingot is completely melted to obtain lithium liquid;
[0007] S2, adding a certain mass of metal element to the lithium liquid, heating and stirring to make the metal element and the lithium liquid react completely to obtain an alloy mixture, wherein the content of the metal element does not exceed 50wt%;
[0008] S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot after cooling;
[0009] S4, rolling and cutting the alloy ingot to obtain a sheet;
[0010] S5. Place the sheet in a dry air or inert gas atmosphere, raise the temperature to 100-150°C and keep it warm for 0.5-4h;
[0011] S6. Take out the sheet and cool it to room temperature to obtain a lithium-rich alloy.
[0012] Preferably, in the lithium-rich alloy, the content of metal elements is 0.5wt% to 50wt%.
[0013] Preferably, in step S1, the heating time is 30±5 min.
[0014] Preferably, in step S2, the metal element is Al or Mg.
[0015] Preferably, in step S2, the heating temperature is 300-500°C, the heating time is 60±10min, and the stirring rate is 300-500r / min.
[0016] Preferably, in step S5, the inert gas is argon or nitrogen.
[0017] Preferably, the inert gas is argon gas mixed with oxygen or nitrogen.
[0018] Preferably, in step S5, the heating rate is 5-20°C / min.
[0019] And a lithium-rich alloy for a high-energy-density battery, which is prepared by the above-mentioned method for preparing a lithium-rich alloy for a high-energy-density battery.
[0020] Compared with the prior art, the advantages of the present invention are:
[0021] 1. By heat treating the sheet, the structure of the second phase can be refined and the distribution of the second phase in the electrode can be more uniform, thereby improving the uniformity of nucleation during lithium deposition, inhibiting the formation of lithium dendrites, and helping to improve the cycle performance of lithium metal batteries;
[0022] 2. The heat treatment scheme for the sheet is simple, time-saving and easy to operate, which can greatly simplify the production process, improve production efficiency and speed up the production cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the change in capacity retention rate of the lithium metal battery composed of Example 1;
[0024] Figure 2 A schematic diagram showing the change in capacity retention rate of a lithium metal battery composed of Example 2;
[0025] Figure 3 Schematic diagram of the change in capacity retention rate of the lithium metal battery composed of Comparative Example 1;
[0026] Figure 4 The scanning electron microscope (SEM and EDS) photos of Example 1;
[0027] Figure 5 The scanning electron microscope (SEM and EDS) photos of Example 2;
[0028] Figure 6 The scanning electron microscope (SEM and EDS) photos of Comparative Example 1 are shown. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0030] Example:
[0031] A method for preparing a lithium-rich alloy for a high specific energy battery comprises the following steps:
[0032] S1. Put a certain mass of pure lithium ingot into a stainless steel crucible and heat it to 300-500°C until the pure lithium ingot is completely melted to obtain lithium liquid;
[0033] S2, adding a certain mass of metal element to the lithium liquid, heating and stirring to make the metal element and the lithium liquid react completely to obtain an alloy mixture, wherein the content of the metal element does not exceed 50wt%, preferably 0.5wt% to 50wt%;
[0034] S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot after cooling;
[0035] S4, rolling and cutting the alloy ingot to obtain a sheet;
[0036] S5. Place the sheet in a dry air or inert gas atmosphere, raise the temperature to 100-150°C and keep it warm for 0.5-4h;
[0037] S6. Take out the sheet and cool it to room temperature to obtain a lithium-rich alloy.
[0038] In step S1, the heating time is 30±5 min.
[0039] In step S2, the metal element is Al or Mg, the heating temperature is 300-500°C, the heating time is 60±10min, and the stirring rate is 300-500r / min.
[0040] In step S5, the inert gas is argon or nitrogen, and the heating rate is 5-20°C / min.
[0041] When argon is used as the inert gas, oxygen or nitrogen may be mixed in the argon to form a protective layer rich in Li2O or Li3N on the surface of the sheet.
[0042] Embodiment 1,
[0043] A method for preparing a lithium-rich alloy for a high specific energy battery comprises the following steps:
[0044] S1. Put 95g of pure lithium ingot into a stainless steel crucible and heat it to 350°C for 30 minutes until the pure lithium ingot is completely melted to obtain lithium liquid;
[0045] S2, adding 5 g of aluminum particles into the lithium liquid, heating and stirring at a heating temperature of 350° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the aluminum particles to react completely with the lithium liquid to obtain an alloy mixture;
[0046] S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot with an Al content of 5wt% after cooling;
[0047] S4, rolling and cutting the alloy ingot to obtain a sheet with a thickness of 60 μm;
[0048] S5, placing the sheet in an Ar atmosphere, heating it to 120°C at a heating rate of 10°C / min and keeping it at that temperature for 2h;
[0049] S6. Take out the sheet and cool it to room temperature to obtain a lithium-rich alloy.
[0050] Embodiment 2,
[0051] The rest is the same as that of Example 1, except that in step S5, the insulation temperature is 150°C.
[0052] Embodiment 3,
[0053] The rest is the same as that of Example 1, except that in step S5, the insulation temperature is 100°C.
[0054] Embodiment 4,
[0055] The rest is the same as Example 1, except that in step S5, the insulation time is 0.5 h.
[0056] Embodiment 5,
[0057] The rest is the same as Example 1, except that in step S5, the insulation time is 4 hours.
[0058] Embodiment 6,
[0059] A method for preparing a lithium-rich alloy for a high specific energy battery comprises the following steps:
[0060] S1. Put 85g of pure lithium ingot into a stainless steel crucible and heat it to 350°C for 30 minutes until the pure lithium ingot is completely melted to obtain lithium liquid;
[0061] S2, adding 15g of aluminum particles into the lithium liquid, heating and stirring at a heating temperature of 350°C, a heating time of 60min, and a stirring rate of 400r / min to allow the aluminum particles and the lithium liquid to react completely to obtain an alloy mixture;
[0062] S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot with an Al content of 15wt% after cooling;
[0063] S4, rolling and cutting the alloy ingot to obtain a sheet with a thickness of 60 μm;
[0064] S5, placing the sheet in an Ar atmosphere, heating it to 120°C at a heating rate of 10°C / min and keeping it at that temperature for 2h;
[0065] S6. Take out the sheet and cool it to room temperature to obtain a lithium-rich alloy.
[0066] Embodiment 7,
[0067] The rest is the same as Example 1, except that magnesium blocks are used instead of aluminum particles.
[0068] Embodiment 8,
[0069] The rest is the same as Example 6, except that magnesium blocks are used instead of aluminum particles.
[0070] Embodiment 9,
[0071] The rest is the same as that of Example 1, except that in step S5, oxygen is mixed in the Ar gas atmosphere.
[0072] Embodiment 10
[0073] The rest is the same as that of Example 1, except that in step S5, nitrogen is mixed in the Ar gas atmosphere.
[0074] Comparative Example 1
[0075] S1. Put 95g of pure lithium ingot into a stainless steel crucible and heat it to 350°C for 30 minutes until the pure lithium ingot is completely melted to obtain lithium liquid;
[0076] S2, adding 5 g of aluminum particles into the lithium liquid, heating and stirring at a heating temperature of 350° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the aluminum particles to react completely with the lithium liquid to obtain an alloy mixture;
[0077] S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot with an Al content of 5wt% after cooling;
[0078] S4. The alloy ingot is rolled and cut to obtain a lithium alloy with a thickness of 60 μm.
[0079] Comparative Example 2
[0080] A method for preparing a lithium-rich alloy comprises the following steps:
[0081] S1. Put 85g of pure lithium ingot into a stainless steel crucible and heat it to 350°C for 30 minutes until the pure lithium ingot is completely melted to obtain lithium liquid;
[0082] S2, adding 15g of aluminum particles into the lithium liquid, heating and stirring at a heating temperature of 350°C, a heating time of 60min, and a stirring rate of 400r / min to allow the aluminum particles and the lithium liquid to react completely to obtain an alloy mixture;
[0083] S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot with an Al content of 15wt% after cooling;
[0084] S4. The alloy ingot is rolled and cut to obtain a lithium alloy with a thickness of 60 μm.
[0085] Comparative Example 3
[0086] The rest is the same as that of Comparative Example 1, except that magnesium blocks are used instead of aluminum particles.
[0087] Comparative Example 4
[0088] The rest is the same as that of Comparative Example 2, except that magnesium blocks are used instead of aluminum particles.
[0089] The lithium-rich alloys prepared in Examples 1-10 and the lithium alloys prepared in Comparative Examples 1-4 were die-cut according to the size of the required assembled battery to obtain negative electrode sheets, and the negative electrode sheets, battery separators, electrolytes and ternary NCM6 systems were assembled into lithium metal batteries. All lithium metal batteries were subjected to charge and discharge cycle tests. The test environment was 25°C, the voltage test range was 3.0V to 4.35V, the charge rate was 0.2C, the discharge rate was 1.0C, and the number of cycles when the capacity retention rate was less than 80% or failure phenomena such as short circuit overcharging occurred were recorded. The test data are as follows:
[0090]
[0091]
[0092] According to the test results of Example 1, Examples 6-8, Comparative Examples 1-4 and the attached Figure 1 and attached Figure 3 It can be seen that compared with conventional lithium alloys, when the lithium-rich alloy obtained by heat treatment is used as a negative electrode, the number of cycles of the lithium metal battery can be increased by more than 26.2%, reaching a maximum of 66.7%, and the cycle performance is significantly improved.
[0093] According to the test results of Examples 1-5 and Comparative Example 1 and the attached Figure 1-3 It can be seen that by regulating the heat treatment atmosphere, holding temperature and holding time, the mechanical strength of the lithium-rich alloy can be effectively improved, the uniformity and surface smoothness of the lithium-rich alloy can be improved, and the reversibility of lithium dissolution / deposition during the charge and discharge process can be improved, ultimately significantly improving the cycle performance of the lithium metal battery.
[0094] According to the test results of Example 1 and Examples 9-10, during the heat treatment process, the oxygen or nitrogen mixed in the atmosphere can form a protective layer rich in Li2O or Li3N with the Li in the sheet. The formation of the protective layer helps to improve the stability of the lithium-rich alloy, thereby improving the cycle performance of the lithium metal battery. Among them, the stability of the lithium-rich alloy rich in the Li3N protective layer is better than that of the lithium-rich alloy rich in the Li2O protective layer.
[0095] See attached Figure 4 The second phase in the heat-treated lithium-rich alloy is in the form of strips with a length of 5-15 μm and a width of 2-3 μm, see Appendix Figure 5 The second phase in the heat-treated lithium-rich alloy is in the form of strips with a length of 2-10 μm and a width of 1-2 μm, see Figure 6 The second phase in the unheat-treated lithium alloy is in the form of strips with a length of 10-50μm and a width of 2-5μm. It can be seen that the lithium-rich alloy obtained by heat treatment has more second phases and a more uniform distribution. With the increase of heat treatment temperature and time, the amount and uniformity of the second phase distribution can be increased, and the size of the second phase particles can be reduced, which is beneficial to improving the cycle performance of lithium metal batteries.
[0096] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a lithium-rich alloy for a high specific energy battery, characterized in that: The following steps are involved: S1. Put a certain mass of pure lithium ingot into a stainless steel crucible and heat it to 300-500°C until the pure lithium ingot is completely melted to obtain lithium liquid; S2, adding a certain mass of metal element to the lithium liquid, heating and stirring to make the metal element and the lithium liquid react completely to obtain an alloy mixture, wherein the content of the metal element does not exceed 50wt%; S3, casting the alloy mixture into a stainless steel mold, and obtaining an alloy ingot after cooling; S4, rolling and cutting the alloy ingot to obtain a sheet; S5. Place the sheet in a dry air or inert gas atmosphere, raise the temperature to 100-150°C and keep it warm for 0.5-4h; S6. Take out the sheet and cool it to room temperature to obtain a lithium-rich alloy.
2. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 1, characterized in that: In the lithium-rich alloy, the content of the metal element is 0.5wt% to 50wt%.
3. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 1, characterized in that: In step S1, the heating time is 30±5 min.
4. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 1, characterized in that: In the step S2, the metal element is Al or Mg.
5. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 1, characterized in that: In step S2, the heating temperature is 300-500°C, the heating time is 60±10min, and the stirring rate is 300-500r / min.
6. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 1, characterized in that: In the step S5, the inert gas is argon or nitrogen.
7. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 6, characterized in that: The inert gas is argon mixed with oxygen or nitrogen.
8. The method for preparing a lithium-rich alloy for a high specific energy battery according to claim 1, characterized in that: In step S5, the heating rate is 5-20°C / min.
9. A lithium-rich alloy for a high specific energy battery, characterized in that: The lithium-rich alloy is prepared by the method for preparing a lithium-rich alloy for a high-energy-density battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
A lithium alloy anode material and its preparation method
CN109326792B